(untitled) (Journal of the Bangladesh Agricultural University, 2018)
A floristic survey has been carried out from January 2015 to January 2016 to investigate the species diversity of Cyperaceous weeds present at Bangladesh Agricultural University campus. A total of 48 species belonging to 11 genera has been collected and identified. Among these, the prominent genus was Fimbristylis (13 species) followed by Cyperus (12 species) and three genera viz. Actinoscirpus, Bolboshoenus and Fuirena were represented by single species. Result of the present study revealed that some of these species are major and common obnoxious weeds in different crop fields. A good number of these species have great medicinal uses, fodder, raw materials for small industries and other economic values. The detailed taxonomic studies of these weeds will be helpful for the management practices of Cyperaceous weeds at this campus as well as in the whole country. It might be concluded that development of improved cultivation procedures will be helpful for getting high economic benefits from Cyperaceous weeds without affecting our crop yield and agro-ecosystem. There is no direct evidence of climate change threatening or eliminating Cyperaceae taxa from this locality. J. Bangladesh Agril. Univ. 16(2): 221-226, August 2018